Interactivity and interactions in e-learning - Implementation within a blended-learning scenario - Roznawski, N.; Wiemeyer, J. (International Journal of Computer Science in Sport, 2008)
Interactive features denote one of the most important surplus values of e-learning. In the scientific discussion interaction and interactivity are distinguished. Numerous options are available to enhance interaction and interactivity in e-learning. In this contribution we report on an e-learning project that tries to implement interaction and interactivity using a blended-learning scenario which is based on a specific didactical approach. Online and offline phases as well as single and team work are merged. First results of formative evaluations are promising. The students appreciate the course and particularly the interactive features. In the future, summative evaluations will show whether the interactive blended-learning scenario is superior or not.